Characteristics of expansin gene isolated from local soybean cultivar in Vietnam - Son, Lo Thanh; Bich, Bui Ngoc; Thanh Thanh, Nguyen Vu; Mau, Chu Hoang (Academia Journal of Biology, 2013)
Expansin is a protein family, having the function in expanded cell wall, that has been regarded as a major protein affecting the prolongation of root cells in plants. Currently, the role of expansion in the process of development of soybean roots has not been clarified although there have been many research efforts. In this study we present the results of amphification, cloning and determination of the GmEXP1 gene sequence of local soybean Xuan Lang Son cultivar with good drought tolerance. GmEXP1 gene isolated from genome of Xuan Lang Son soybean cultivar had the size of 1068 nucleotides, in which the coding region had 768 nucleotides, with two exons and one intron. Size of exon 1 was 467 bp; exon 2 was 301 bp; intron of 300 bp. GmEXP1 gene encoding 255 amino acids. The comparison with GmEXP gene (Accession AF516879 on GenBank), showed that GmEXP1 gene of Xuan Lang Son soybean cultivar had 17 different nucleotide positions and 8 amino acid positions; DPBB region and Pollen allerg of deduced protein had three  changed amino acid positions. The rele of these changes in development of the roots as well as the level of drought tolerance of soybean need to be further studied.